2020
DOI: 10.1002/anie.201916480
|View full text |Cite
|
Sign up to set email alerts
|

Isothiourea‐Catalyzed Atropselective Acylation of Biaryl Phenols via Sequential Desymmetrization/Kinetic Resolution

Abstract: Axially chiral phenols are attractive targets in organic synthesis.T his motif is central to many natural products and widely used as precursors to,ordirectly,aschiral ligands and catalysts.D espite their utility few simple catalytic methods are available for their synthesis in high enantiopurity.Herein the atropselective acylation of ar ange of symmetric biaryl diols is investigated using isothiourea catalysis.S tudies on amodel biaryl diol substrate shows that the high product er observed in the process is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 92 publications
0
19
0
2
Order By: Relevance
“…On apreparative scale,and using i-Pr 2 NEt as the organic base,( S)-6 was isolated in 32 %y ield and 94:6 er (entry 11), with the absolute configuration of 6 confirmed by X-ray analysis. [27] Thea lternative isothiourea HyperBTM 9 gave asimilar product ratio but provided (S)-6 in reduced er (85:15 er, entry 12). In-situ reaction monitoring of the enantioselective acylationo fd iol 1 indicated that the er of product (S)-6 increased with reaction conversion (see SI for further information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On apreparative scale,and using i-Pr 2 NEt as the organic base,( S)-6 was isolated in 32 %y ield and 94:6 er (entry 11), with the absolute configuration of 6 confirmed by X-ray analysis. [27] Thea lternative isothiourea HyperBTM 9 gave asimilar product ratio but provided (S)-6 in reduced er (85:15 er, entry 12). In-situ reaction monitoring of the enantioselective acylationo fd iol 1 indicated that the er of product (S)-6 increased with reaction conversion (see SI for further information).…”
Section: Resultsmentioning
confidence: 99%
“…Notably,f or the series of C(2')heteroatom derivatives,( S)-BTM 8 proved the optimal catalyst, giving (S)-monoesters 32-34 in excellent (92:8-95:5) er in each case.T he absolute configuration of 32 was confirmed by X-ray crystallographic analysis. [39] Theu se of (2R,3S)-HyperBTM 9 gave the opposite (R)-enantiomer of C(2')-halogen-substituted monoesters 32 and 33,h owever 32 and 33 were obtained in both reduced yield and er.…”
Section: A1 5-o•••s Interaction Within Acylatedi Sothioureas Is Widementioning
confidence: 99%
See 2 more Smart Citations
“…A seminal contribution by Hayashi and co-workers 7 is based on this strategy: starting from achiral biaryl bistriflates, an enantioselective Kumada coupling was developed by using PdCl 2 [(S)-Phephos] [Phephos = 2-(dimethylamino)-1-(diphenylphosphino)-3-phenylpropane] as the catalyst (Scheme 4A). More recently, Cheong, Smith and co-workers 8 have exploited chiral bases BTM and HyperBTM as acyl transfer catalysts for the acylative desymmetrization of biaryl diols (Scheme 4B). Remarkably, a divergent stereoselectivity was observed depending on the substitution pattern of the substrate and the catalyst used.…”
Section: Desymmetrization Of Substrates With Restricted Rotation Of the Prochiral Axismentioning
confidence: 99%